2020
DOI: 10.3390/jcm9020377
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Diagnosis as a Disease Predictor

Abstract: Background: Saliva, the most readily available body fluid, is the product of genes which are in constant activity throughout life. Measurement of saliva can predict the onset of some diseases years before their accumulation in vulnerable tissues causes clinical signs to appear. The purpose of this study was is to demonstrate current applications of saliva analysis and to predict and prevent disease progression. Methods: We measured levels of Abeta42, C-reactive proteins (CRPs), and tumornecrosis factors (TNFs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This study focused on salivary metabolites since their non-invasive collection would provide benefit as a clinical test. Non-metabolite biomarkers, such as C-reactive proteins and tumor necrosis factors in saliva, were elevated in the subjects with AD or coronary heart diseases compared to healthy controls, which indicates that these markers showed no specificity to AD [ 33 ]. However, the mechanisms underlying the effect of ischemia on BDNF signaling remain unclear in our study, and thus, a comprehensive analysis of metabolites is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focused on salivary metabolites since their non-invasive collection would provide benefit as a clinical test. Non-metabolite biomarkers, such as C-reactive proteins and tumor necrosis factors in saliva, were elevated in the subjects with AD or coronary heart diseases compared to healthy controls, which indicates that these markers showed no specificity to AD [ 33 ]. However, the mechanisms underlying the effect of ischemia on BDNF signaling remain unclear in our study, and thus, a comprehensive analysis of metabolites is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva components have the potential to be used as biomarkers for several diseases [ 30 ], including dementia [ 31 ]; blood may also be used [ 32 ]. The measurement of salivary components can predict the onset of fatal disease [ 33 ]. In humans, the concentration of amyloid-β [ 32 , 34 ] and tau [ 35 ] in saliva reflected cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is necessary to normalize the data obtained in each group to avoid errors associated with the raw data [126,128]. Traditionally, many researchers use the p-value as the main statistical tool in order to identify analytes whose variation is statistically significant [129][130][131][132]. However, this approach is extremely limited and often results in numerous false positives and negatives [133,134].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, salivary Aβ 1-42 level in AD patients was greater than the high-level control group. These data demonstrated that measuring salivary Aβ 1-42 levels can diagnose AD and indicate as well as that it may predict the risk of future onset [ 47 ].…”
Section: Biomarkers In the Diagnosis Of Alzheimer’s Diseasementioning
confidence: 99%